E-UKBM Ethno-STEM: The Development of Independent Learning Activities to Train Students’ Critical Thinking Skills in Pressure Topics - Setiyani, Anisa; Sudarmin, Sudarmin; Ellianawati, Ellianawati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This study aims to determine the effectiveness, feasibility, and influence of the Ethno-STEM Independent Learning Activity Unit (UKBM) in improving students’ critical thinking skills. This type of research is R&D with the ADDIE type. The research sample used a purposive sampling technique in small-scale and large-scale trials at one of the private junior high schools in Salatiga City. The results of the study show that 1) e-UKBM Ethno-STEM has the characteristics of implementing an ethnoscience aspect that links scientific knowledge with local wisdom, studying science through local wisdom in a balanced way, guided by the Merdeka Curriculum and the 2013 Curriculum by using a scientific approach; 2) Ethno-STEM e-UKBM is suitable for use in science learning on substance stress; 3) e-UKBM Ethno-STEM can improve critical thinking skills with an N-Gain value of 72.27% in the high category; 4) e-UKBM Ethno-STEM has an effect on critical thinking skills with a t-count of 10.87. Based on the results of this study, it can be concluded that e-UKBM Ethno-STEM is appropriate to be used to improve student’s critical thinking skills in substance stress study materials.